Sociolinguistic Phenomenon of Indolish (Indonesian-English) Codeswitching by Lecturers to Students in Classroom Teaching Activities at UBG - Abdul Muhid; Zainudin Abdussamad; Sutarman Sutarman; Diah Supatmiwati; Wiya Suktiningsih; Syamsurrijal Syamsurrijal (LPPM Universitas Bumigora Mataram, 2022)
The current issue of research is aimed at finding the forms and function of code-switching by the lecturers of Computer science, and management. The appropriate method used in this research is qualitative by involving two approaches: linguistic constraints and sociolinguistic functions. The data were taken through observation and interview. The findings indicate that the linguistic constraints used by the lecturers are mostly imperative sentence in the form of the words, phrases, and sentences, the functions are as the warning and commanding. While quotations in the forms of words, and phrases which function as actualizing the terms used in the book and article to ease the students to comprehend. The linguistic function found was the speech from lecturer to students in classroom whilst teaching to ease the comprehensions of the students. Key words: sociolinguistic, Indo-lish, Code-switching, teaching.